PENGARUH DIABETES SELF - MANAGEMENT EDUCATION (DSME) TERHADAP KADAR HbA1C - Ismansyah Ismansyah; Lukman Nulhakim; Rivan Firdaus; Indah Nur Imamah; Reheme Zam Zam Shiera Banu; Tia Puspita Anjani (Poltekkes Kemenkes Kalimantan Timur, 2020)
Background : Diabetes Self Management Education is a sustainable and comprehensive family-based treatment that involves families in clients' homes with the aim of increasing, maintaining and maximizing client independence and reducing the impact of diabetes. This study aims to determine the effect of DSME towards diabetic patients on HbA1C levels of type 2 diabetes mellitus clients in the working area of Wonorejo Public Health Center, Samarinda. Method : The design of this study was a quasi-experimental design with a pre and post test with control group design. The population in the study were all patients with diabetes mellitus type 2 in the working area of Wonorejo Public Health Center Samarinda with a total of 32 respondents, by using Simple Random Sampling. The researcher divided the respondents into two groups. Data were analyzed using paired T-Test and Independent T-tests. Result : The results of this study indicate that the results of statistical tests using the Paired TTest, in the experimental group p = 0,001 and p = 0,002 in the control group, while the P value on Independent T-Test is 0,728 (p>α;α=0,05). Conclusion : There is an influence of DSME on HbA1C levels of patients with DM type 2 in the working area of Wonorejo Public Health Center, Samarinda. It is recommended that health workers can make DSME as a reference in providing health promotion interventions to control HbA1C levels of patients with DM type 2.